2021
DOI: 10.3748/wjg.v27.i21.2850
|View full text |Cite
|
Sign up to set email alerts
|

Insight into molecular mechanisms underlying hepatic dysfunction in severe COVID-19 patients using systems biology

Abstract: BACKGROUND The coronavirus disease 2019 (COVID-19), a pandemic contributing to more than 105 million cases and more than 2.3 million deaths worldwide, was described to be frequently accompanied by extrapulmonary manifestations, including liver dysfunction. Liver dysfunction and elevated liver enzymes were observed in about 53% of COVID-19 patients. AIM To gain insight into transcriptional abnormalities in liver tissue of severe COVID-19 patients that may result in liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
1
10
0
1
Order By: Relevance
“…We found that this protein was significantly higher in COVID-19 patients (P < 1.5×10 -14 ) across all three outcomes. HDGF has been shown to be significantly upregulated in transcriptome of liver autopsy samples of severe COVID-19 patients ( 35 ). We found high HDGF levels in our COVID-19 patients across all three outcomes (P < 4.1×10 -14 ).…”
Section: Resultsmentioning
confidence: 99%
“…We found that this protein was significantly higher in COVID-19 patients (P < 1.5×10 -14 ) across all three outcomes. HDGF has been shown to be significantly upregulated in transcriptome of liver autopsy samples of severe COVID-19 patients ( 35 ). We found high HDGF levels in our COVID-19 patients across all three outcomes (P < 4.1×10 -14 ).…”
Section: Resultsmentioning
confidence: 99%
“…As it is a systemic inflammatory disease, COVID-19 affects, among others, the gastrointestinal system ( 48 ). Individuals who developed the severe form of the disease had pathological tissue changes in the liver parenchyma, developing liver cirrhosis and non-alcoholic liver steatosis ( 49 ). An increased liver parenchyma density is suggestive of hepatic steatosis and was observed in 57% of individuals in Group 1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study indicated that SARS-CoV-2 may hijack the GPCR signaling pathway to alter fluid and ion transport within the lungs, which leads to lung edema-a deadly clinical sign of COVID-19 infection (58). Similarly, Hammoudeh et al (59) suggested that SARS-CoV-2 manipulation of the GPCR pathways could facilitate viral infection within the host leading to dysregulation of intracellular transport within the livers of infected patients. Given its role in infectivity of other coronaviruses, further investigation into GPCR signaling and its association with BCoV and BRD in cattle is warranted.…”
Section: Discussionmentioning
confidence: 99%